Roles of IFN-γ and γδ T Cells in Protective Immunity Against Blood-Stage Malaria - Inoue, Shin-Ichi; Niikura, Mamoru; Mineo, Shoichiro; Kobayashi, Fumie (Frontiers in Immunology, 2013)
Malaria is caused by infection with Plasmodium parasites. Various studies with knockout mice have indicated that IFN-γ plays essential roles in protective immunity against blood-stage Plasmodium infection. However, after Plasmodium infection, increased IFN-γ production by various types of cells is involved not only in protective immunity, but also in immunopathology. Recent reports have shown that IFN-γ acts as a pro-inflammatory cytokine to induce not only the activation of macrophages, but also the generation of uncommon myelolymphoid progenitor cells after Plasmodium infection. However, the effects of IFN-γ on hematopoietic stem cells and progenitor cells are unclear. Therefore, the regulation of hematopoiesis by IFN-γ during Plasmodium infection remains to be clarified. Although there are conflicting reports concerning the significance of γδ T cells in protective immunity against Plasmodium infection, γδ T cells may respond to infection and produce IFN-γ as innate immune cells in the early phase of blood-stage malaria. Our recent studies have shown that γδ T cells express CD40 ligand and produce IFN-γ after Plasmodium infection, resulting in the enhancement of dendritic cell activation as part of the immune response to eliminate Plasmodium parasites. These data suggest that the function of γδ T cells is similar to that of NK cells. Although several reports suggest that γδ T cells have the potential to act as memory cells for various infections, it remains to be determined whether memory γδ T cells are generated by Plasmodium infection and whether memory γδ T cells can contribute to the host defense against re-infection with Plasmodium. Here, we summarize and discuss the effects of IFN-γ and the various functions of γδ T cells in blood-stage Plasmodium infection.